REPRESENTASI ALAM DALAM NOVEL SRIMENANTI KARYA JOKO PINURBO: EKOKRITIK GERD GARRARD - M, Asia,; Ridwan, Ridwan; Mustika, Indah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyse the ecological representation in the novel ‘Srimenanti’ by Joko Pinurbo using Greg Garrard's ecocritical theory. Ecocriticism is one of the theories in literary studies that examines the relationship between literary works and nature and the environment. This approach focuses on how nature is depicted in literature, as well as the impact of human activities on the environment. In ecocritical theory, nature is considered an active agent that interacts with culture, and literary works can be a means to criticise ecological damage and illustrate the interdependence between humans and the environment. This research is important because it can show how literature, such as Joko Pinurbo's, reflects ecological awareness through vivid images of nature and its social relevance. Joko Pinurbo, known as a poet with a simple yet profound language style, often depicts his closeness to nature and social problems related to the exploitation of nature. By using an ecocritical approach, Pinurbo's works can be interpreted as reflections on human relationships with nature as well as criticism of environmental degradation. Therefore, Joko Pinurbo's works have significant relevance in the discourse of literature and ecology, and are important to be further analysed through an ecocritical perspective to understand more deeply their influence on people's ecological awareness.